Voiding recovery after radical parametrectomy in cervical cancer patients: An international prospective multicentre trial - SENTIX - Zapardiel, Ignacio; Kocian, Roman; Köhler, Cristhardt; Klat, Jaroslav; Germanova, Anna; Jacob, Anna; Bajsova, Sylva; Böhmer, Gerd; Lay, Laura; Gil-Ibañez, Blanca; Havelka, Pavel; Kipp, Barbara; et al. (Gynecologic oncology, 2021)
OBJECTIVE: Voiding dysfunctions represent a leading morbidity after radical hysterectomy performed in patients with early-stage cervical cancer. The aim of this study was to perform ad hoc analysis of factors influencing voiding recovery in SENTIX (SENTinel lymph node biopsy in cervIX cancer) trial. METHODS: The SENTIX trial (47 sites, 18 countries) is a prospective study on sentinel lymph node biopsy without pelvic lymphadenectomy in patients with early-stage cervical cancer. Overall, the data of 300 patients were analysed. Voiding recovery was defined as the number of days from surgery to bladder catheter/epicystostomy removal or to post-voiding urine residuum ≤50 mL. RESULTS: The median voiding recovery time was three days (5th-95th percentile: 0-21): 235 (78.3%) patients recovered in <7 days and 293 (97.7%) in <30 days. Only seven (2.3%) patients recovered after >30 days. In the multivariate analysis, only previous pregnancy (p = 0.033) and type of parametrectomy (p < 0.001) significantly influenced voiding recovery >7 days post-surgery. Type-B parametrectomy was associated with a higher risk of delayed voiding recovery than type-C1 (OR = 4.69; p = 0.023 vs. OR = 3.62; p = 0.052, respectively), followed by type-C2 (OR = 5.84; p = 0.011). Both previous pregnancy and type C2 parametrectomy independently prolonged time to voiding recovery by two days. CONCLUSIONS: Time to voiding recovery is significantly related to previous pregnancy and type of parametrectomy but it is not influenced by surgical approach (open vs minimally invasive), age, or BMI. Type B parametrectomy, without direct visualisation of nerves, was associated with longer recovery than nerve-sparing type C1. Importantly, voiding dysfunctions after radical surgery are temporary, and the majority of the patients recover in less than 30 days, including patients after C2 parametrectomy.
Keywords: senioři; Nerve-sparing techniques; Cervical cancer; Middle Aged; Hysterectomy; Adult; Prospective Studies; nádory děložního čípku; Parametrectomy; Radical hysterectomy; ženské pohlaví; Humans; prospektivní studie; lidé středního věku; Uterine Cervical Neoplasms; hysterektomie; dospělí; Female; Aged; Voiding recovery; lidé